All Days 2016
DOI: 10.2118/181041-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Smart Digital Platform for Effective Well Control Management

Abstract: The oil and gas industry has increased its efforts in preventing and mitigating risks associated with loss of well control and loss of primary containment. Initiatives have primarily focused on increasing the awareness and education of field and operations personnel. The foundation of this strategy rests on the belief that increased awareness of threats, risks and enhanced training will lower well control risks and eliminate well control events. Despite this renewed focus, industry data show that well control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…The results also show that in the Western and Northern region of the EU, the relationship between the two indicators was stronger compared to the other EU regions. The findings of the present paper are generally in line with the findings of some previous studies that showed a positive relationship between digital technologies and people's satisfaction and well-being [33,45], but it must be specified that no other study has made a link between DESI and WHI at the EU level. Overall, the relationship between DESI and WHI appears to have been stronger in 2020 compared to 2019 but weaker in 2021 compared to 2020 and 2019.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results also show that in the Western and Northern region of the EU, the relationship between the two indicators was stronger compared to the other EU regions. The findings of the present paper are generally in line with the findings of some previous studies that showed a positive relationship between digital technologies and people's satisfaction and well-being [33,45], but it must be specified that no other study has made a link between DESI and WHI at the EU level. Overall, the relationship between DESI and WHI appears to have been stronger in 2020 compared to 2019 but weaker in 2021 compared to 2020 and 2019.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, these technologies can increase people's professional motivation and job satisfaction. Thus, digital technologies help to increase productivity, quality and efficiency in production activities and allow for monitoring and risk reduction [45]. Similarly, they increase performance in marketing activities by enabling efficient product placement and reducing price dispersion [46] and they improve quality of services in hospitals [47].…”
Section: Happiness and Digital Technologiesmentioning
confidence: 99%
“…The Abu Dhabi research provides evidence of multiple correlates and associates of digital technology, our happiness, and our daily life. Results are consistent with other empirical findings that the use of digital technology has positive strategic effects on society and hence indirectly on our happiness (Choudhury & Barman, 2014;Devaraj & Kohli, 2003;Jensen, 2007;Jose et al, 2016). Results also confirm the association of happiness with daily happenings, including our psychological and physical feelings (Bangun et al, 2021).…”
Section: B Discussionsupporting
confidence: 90%
“…The use of digital technology in the industry has become commonplace, used extensively, and, in an increasingly sophisticated fashion, providing many benefits. The use of digital technology in manufacturing, for example, helps to improve productivity, quality, efficiency, monitor and reduce risk, and reduce the effects of human factors (Jose et al, 2016). In the hospital, digital technology usage was positive and significantly affected quality and revenue (Devaraj and Kohli, 2003).…”
Section: Digital Technology and Performancementioning
confidence: 99%